Professional wrestling : sport and spectacle - Mazer, Sharon (Performance Studies Ser., 2020)
"The book explores professional wrestling as theatrical performance. First published in 1998, this new edition both preserves the original's snapshot of the wrestling scene of the 1980s and 1990s and features an up-to-date perspective on the current state of play"--